Pengaruh Pendidikan Kesehatan terhadap Tingkat Pengetahuan Remaja tentang Bahaya Pernikahan Dini - Margaretha Eva Millenia; ‪Fitriani Ningsih; Lensi Natalia Tambunan (Jurnal Surya Medika (JSM), 2022)
In the current era of globalization, many adolescent problems occur resulting in early marriage behavior such as lack of adolescent knowledge, self-desire due to feelings of love, low socioeconomic circumstances, low education, free association, lack of parental care, and negative influence of mass media/information. One of the factors that influence the incidence of early marriage is knowledge. A lack of knowledge about sexual and reproductive health information and education in adolescents causes them to lack the skills to make informed and safe decisions about sexual and reproductive risks, thus enabling premarital sex and leading to early marriage. The factors that can influence the increase in knowledge are information received such as health education. This study aims to determine the effect of health education on the level of knowledge of adolescents about the dangers of early marriage based on data through the literature review method. Using the literature review method. Search journals using an academic database, namely Google Scholar which was published in 2017-2021 using Indonesian and English. Research design Eksperimental. There are 6 journals that state the influence of health education on the level of knowledge of adolescents about the dangers of early marriage is shown from the results of experimental tests after being given health education experienced a significant increase in knowledge. The provision of Health Education greatly affects the knowledge of someone who previously did not know to know, therefore education about early marriage should continue to be given to adolescents in order to avoid the negative impact of early marriage.